Use of Delphi-AHP neutrosophic methods for the analysis of school indicators - Alex Fabian Solano Moreno; Carlos Javier Lizcano Charpeta; Beatrice Del Carmen Viteri Naranjo; Jean Pierre Ramos-Carpio (Neutrosophic Sets and Systems)
The study addresses the complex task of analyzing school indicators through the combined application of the Delphi-AHP neutrosophic methods, seeking to overcome the limitations of traditional approaches in educational assessment. The research focuses on the urgent need to develop more robust models that can handle the uncertainty, imprecision, and ambiguity inherent in educational data. Although previous research has been conducted on the analysis of school indicators, conventional approaches fail to effectively integrate the multiple dimensions and degree of uncertainty of the data. This study proposes an innovative solution by integrating neutrosophic tools, which allow for a more flexible and detailed analysis of indicators, considering various perspectives and situations. The use of the Delphi-AHP method, complemented by a neutrosophic perspective, allows for capturing the complexity of the educational environment and generating more accurate and realistic assessments. Through a series of consultation and weighting rounds, results were obtained that highlight the importance of factors such as the social context, educational infrastructure and the participation of actors involved in the school process. The findings not only enrich the theoretical field by applying a neutrosophic approach to the analysis of school indicators but also offer practical applications to improve educational policies and decision-making. This study contributes significantly to the advancement of educational data analysis by providing a more adaptable and accurate methodological framework for future research and practice in the school setting.